Case report: Concurrent occurrence of salmonellosis, colibaccillosis and histomoniasis in a broiler flock fed with antibiotic-free commercial feed - Ganapathy, K.; Salamat, M.H.; Lee, C.C.; Johara, M.Y. (Taylor and Francis Group, 2000)
A flock of 3-week-old broiler chickens fed with antibiotic-free commercial feed developed cyanotic combs, depression, extended abdomens, reddened abdominal skin, faeces-stained vents, and diarrhoea. By the end of week 6, mortality reached 19.3%, and important lesions seen were ascites, airsacculitis, swollen/congested kidneys, fibrinous perihepatitis, fibrinous pericarditis with or without hydropericardium, haemorrhagic enteritis-typhilitis and ballooned caeca. Salmonella typhmurium var Copenhagen and Escherichia coli were isolated from livers, hearts, intestines and caeca. Histomonas spp. were detected only in caeca. Thus, concurrent occurrence of salmonellosis, colibacillosis and histomoniasis was diagnosed.